2018
DOI: 10.3390/ijms19010124
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Shock Wave Therapy Alters the Expression of Fibrosis-Related Molecules in Fibroblast Derived from Human Hypertrophic Scar

Abstract: Extracorporeal shock wave therapy (ESWT) considerably improves the appearance and symptoms of post-burn hypertrophic scars (HTS). However, the mechanism underlying the observed beneficial effects is not well understood. The objective of this study was to elucidate the mechanism underlying changes in cellular and molecular biology that is induced by ESWT of fibroblasts derived from scar tissue (HTSFs). We cultured primary dermal fibroblasts derived from human HTS and exposed these cells to 1000 impulses of 0.03… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 46 publications
1
41
0
Order By: Relevance
“…The authors hypothesized that focused ESWT might work anti-inflammatorily in this regard. Even an interaction with the numerous cytokines as well as with CGRP appears feasible [78,79].…”
Section: Extracorporeal Shockwave Therapy (Eswt)mentioning
confidence: 99%
“…The authors hypothesized that focused ESWT might work anti-inflammatorily in this regard. Even an interaction with the numerous cytokines as well as with CGRP appears feasible [78,79].…”
Section: Extracorporeal Shockwave Therapy (Eswt)mentioning
confidence: 99%
“…Some studies have suggested that the increased expression of TGF-ß1 leads to a vicious cycle of SSCT fibrosis in the idiopathic CTS (Chikenji et al, 2014;Gingery et al, 2014). Although the therapeutic mechanisms of ESWT remain unclear, a recent study assessed the expression of fibrosisrelated molecules in fibroblasts derived from human postburn hypertrophic scar tissue after ESWT, revealing significantly reduced expression of TGF-ß1 after ESWT (Cui et al, 2018), which might explain the antiscarring effect of ESWT. The other proposed mechanism of ESWT is that the waves in ESWT dilate blood vessels through enzymatic promotion (Gonkova, Ilieva, Ferriero, & Chavdarov, 2013;Manganotti & Amelio, 2005;Park & Kwon, 2011) and nonenzymatic nitric oxide synthesis (Kwon, Park, Lee, & Chung, 2012), thus inducing neovascularization, increasing the blood supply to the tissue, and activating growth factors.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, targeting both fibroblasts and keratinocytes populations were the novel therapies for scarring . It was shown that extracorporeal shock wave therapy was responsible for the anti‐scarring by suppressing EMT in the post‐burn scars . As such, focus on the dysregulation of injury‐triggered EMT is proved to contribute to HSs treatment.…”
Section: Biotherapy Targeting Epithelial‐mesenchymal Transition Procementioning
confidence: 99%
“…124 It was shown that extracorporeal shock wave therapy was responsible for the anti-scarring by suppressing EMT in the post-burn scars. 125 As such, focus on the dysregulation of injury-triggered EMT is proved to contribute to HSs treatment. Keratin and vimentin are characteristic markers of epithelial cells and mesenchymal cells, respectively, and can serve as indicative markers of EMT processes.…”
Section: Biotherapy Targeting Epithelial-mesenchymal Transition Promentioning
confidence: 99%